EFFORTS TO IMPROVE TEACHER'S PROFESSIONALISM IN THE TEACHING LEARNING PROCESS - Hosaini Hosaini; Alfiandi Zikra; Muslimin Muslimin (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
In the era of nation-building (Indonesia), which is developing today, teachers have an important role in increasing their potential as an effort to improve the intelligence of the nation's generation including guidance on future generations, the back and forth of a nation is determined by an educator. Therefore, a teacher has a direct obligation to supervise and assist the learning process of learners and students. Admittedly or not, teachers will always be an important element that determines the success and failure of an education. Therefore, teachers always play a role in the formation of potential human resources in the field of nation and state development.)(Teachers are second parents who always educate and supervise children, to achieve their goals and life. Therefore, a teacher must have a very high dedication and the profession he chooses is not a side job, because it is recognized or not the teacher who determines the success of the child. The research was conducted at SMA 1 Ibrahimy Sukorejo Situbondo. To collect data is used observation methods, documentation, and interviews. Then the data that has been collected in the form of words is analyzed with qualitative descriptive analysis.) (From the results of discussion and research, the following conclusions were obtained, the professionalism of teachers in the teaching and learning process was good enough, proven by the ability of teachers to make student units, always make good teaching preparations, use props well, and always hold evaluations. Efforts to improve professionalism made by the principal are management, disciplinary supervision and meetings. While the efforts made by teachers are to continue the level of education, reading themselves, and deliberation.) Dalam era pembangunan bangsa (indonesia), yang sedang berkembang saat ini, guru mempunyai peranan penting dalam meningkatkan potensi diri sebagai upaya untuk meningkatkan kecerdasan generasi bangsa termasuk bimbingan pada generasi mendatang, maju mundurnya suatu bangsa ditentukan oleh seorang pendidik. Oleh karena itu seorang guru mempunyai kewajiban secara langsung untuk mengawasi dan membantu proises belajar peserta didik dan anak didik. Diakui atau tidak, guru akan selalu menjadi unsur penting yang menentukan berhasil dan tidaknya suatu pendidikan. Oleh karena itu maka guru selalu berperan dalam pembentukan sumberdaya manusia yang potensial dibidang pembangunan bangsa dan negara. Guru adalah orang kedua setelah orang tua yang selalu mendidik dan memgawasi anak, untuk meraih cita-cita dan tujan hidupnya. Oleh karena itu, seorang guru harus memiliki dedikasi yang sangat tinggi dan profesi yang dipilihnya itu bukan pekerjaan sampingan, sebab diakui atau tidak gurulah yang menentukan keberhasilan anak.Penelitian dilakukan di SMA 1 Ibrahimy Sukorejo Situbondo. Untuk mengumpulkan data digunakan metode observasi, dokumentasi, dan interview. Kemudian data yang telah terkumpul berupa kata-kata dianalisis dengn tekinik analisis deskriptif kualitatif. Dari hasil pemabahasan dan penelitian didapat kesimpulan sebagai berikut, profesionalisme guru dalam proses belajar mengajar sudah cukup baik, terbukti dengan kemampuan guru membuat satpel, selalu membuat persiapan mengajar dengan baik, menggunakan alat peraga dengan baik, dan selalu mengadakan evaluasi.Upaya peningkatan profesionalisme yang dilakukan oleh kepala sekolah adalah penataran, pengawasan kedisiplinan dan rapat.Sedangkan upaya yang dilakukan oleh guru adalah melanjutkan jenjang pendidikan, membaca sendiri, dan musyawarah.